Pengembangan System Informasi E-Commerce Endeavour Entertainment Berbasis Website - Muhammad Ammirul Alwi Aipassa; Muhammad Raka Abdillah Munthe; Erika Andini; Nabila Syakif; Irwan Freddy Josua Purba (Ridwan Institute, 2025)
Development of an e-commerce information system for a digital startup offering photography, videography, and editing services. Endeavor Entertainment is a student initiative to create a digital platform that facilitates online service products. This system is designed based on HTML and CSS. To ensure a responsive, simple, and easily accessible interface through website devices. The main goal is to improve the efficiency of marketing and sales of service products such as photography, videography, editing, and digital content. With a focus on an innovative user experience. The development method involves analyzing user needs, designing prototypes using HTML for page structure and CSS for visual styling, and integrating basic interaction elements without a complex backend. This process is carried out through an iterative approach starting from wireframing to responsiveness testing on various devices. The result is a functional e-commerce system with key features such as a product catalog and ordering formula. Evaluations show increased accessibility and the potential for increasing sales by up to 30% based on initial simulations. However, limitations in HTML and CSS require further development with backend technology for dynamic features such as payments.